Akumulasi Besi (Fe) pada Kerang Hijau di Perairan Tanjung Mas, Semarang - Findiani Dwi Astari; Djamar Tumpal Floranthus Lumban Batu; Isdradjad Setyobudiandi (Jurnal Ilmu Pertanian Indonesia, 2021)
The source of iron in waters can come from human activities that carry out activities such as waste disposal in household and industrial activities. Green mussels containing iron are very dangerous for the shells themselves and for human health if consumed in excess. This study aims to analyze the concentration of iron in green mussel meat, determine the safe limit of green mussel meat for consumption by humans, and calculate the value of bioconcentration factors. This research was conducted in the sea of Tanjung Mas, Semarang. Samples taken in the form of green mussels, sediments, and water were then analyzed for iron concentrations with Atomic Absorption Spectrophotometer. The results of the study showed that the range of iron concentration values in green mussels from July to November was 39–283,97 mg/kg. The range of MTI values for adults was 1.18–4.92, while for children the range was 0.24–0.98. The value of the bioconcentration factor of green mussels and water was 3271–24839, while the value of the bioconcentration factor of green mussels and sediments was 0.010–9.647. Keywords: bioconcentration, green mussels, iron, maximum tolerable intake, Tanjung Mas